Reaching for the Mountains at the End of a Rebelocracy: Changes in Land and Water Access in Colombia's Highlands During the Post-peace Agreement Phase - Betancur-Alarcón, Laura; Krause, Torsten (Frontiers in Environmental Science, 2020)
The armed conflict shaped and determined land-uses, water access and social and environmental norms in highlands regions in Colombia for several decades. The withdrawal of the Revolutionary Armed Forces of Colombia (FARC) after the Peace Agreement with the government of Colombia in 2016, has brought new dynamics in access and uses of land leading to increasingly visible social-environmental impacts across the country. Social and environmental transformations are taking place in Colombia’s highlands and páramo areas, which supply 70% of the country’s freshwater. Yet, there is little understanding how these transformations occur. We conducted ethnographic fieldwork focusing on the experiences of local actors in natural resource access in Combia village, which was controlled by the FARC for over two decades until 2016. Combia is located in the Las Hermosas mountain region in the southwest of the country. Our interviews and revision of local and regional policy documents show how the transition from the social order under FARC control to a State-regulated phase led to an interplay of new actors and new authority figures which in turn reconfigure local land distribution and control over water. The shift of power as a direct result of the peace agreement and the retraction of the FARC reinforces unequal access to land and water, particularly for peasants without land ownership, which ironically has been the core issue in Colombia’s protracted armed conflict.